A Replication Competent HSV-1(McKrae) with a Mutation in the Amino-terminus of Glycoprotein K (gK) is Unable to Infect Mouse Trigeminal Ganglia after Cornea Infection. (8th January 2014) - Saied, Ahmad A.; Chouljenko, V. N.; Subramanian, Ramesh; Kousoulas, K.G.
Abstract: Purpose: To determine the role of the amino terminus of herpes simplex virus-1 (HSV-1) glycoprotein K (gK) in corneal infection, neuroinvasion, and establishment of virus latency in trigeminal ganglia of mice. Methods: The recombinant virus HSV-1 (McKΔgK31-68) was constructed by engineering gK genes encoding gK lacking 38 amino acids immediately after the gK signal sequence. A rescued virus was also produced. Mouse eyes were scarified and infected with 10 5 plaque forming units (PFU) in each eye. Clinical signs of ocular disease were monitored daily. Thirty days postinfection trigeminal ganglia were collected and processed for quantitative PCR (qPCR) analysis of viral DNA and recovery of infectious virions by cell culture of ganglionic tissues. Results: Deletion of the amino terminus of gK encoded by the McKΔgK31-68 mutant virus did not substantially affect its replication kinetics on African green monkey kidney cells (Vero), while it reduced cell-to-cell spread. McK viral infection of scarified mouse corneas with 10 5 PFU produced severe ocular disease. In contrast, McKΔgK31-68 viral infection with 10 5 PFU produced no significant ocular disease symptoms. All ganglia from mice infected with the McK virus produced high numbers of infectious virions upon explant culture in Vero cells, in agreement with qPCR results detecting high number of HSV-1 viral DNA in ganglionic tissues. In contrast, qPCR failed to detect any viral genomes in McKΔgK31-68 ganglia, while two of the ten ganglia revealed the presence of low numbers of infectious virions upon explant culture in Vero cells. Conclusions: The results show that the amino terminus of gK is essential for neuroinvasiveness and acute herpes keratitis in the mouse eye model. It is likely that gK is involved in efficient infection of axonal termini, since mouse eye scarification provided a direct access to the high density of neuronal axons innervating mouse corneas.